To Induce Immune Reconstitution Inflammatory Syndrome or Suppress It: The Spectrum of Mycobacterium genavense in the Antiretroviral Era. (18th June 2020) - Manion, Maura; Lynn, Niamh; Pei, Luxin; Hammoud, Dima A; Laidlaw, Elizabeth; Roby, Gregg; Metzger, Dorinda; Mejia, Yolanda; Lisco, Andrea; Zelazny, Adrian; Holland, Steve; Vachon, Marie-Louise; et al.
Abstract: Mycobacterium genavense is a challenging opportunistic pathogen to diagnose and manage in patients with human immunodeficiency virus (HIV). Persistent immunosuppression or protracted immune reconstitution inflammatory syndrome can lead to complicated clinical courses. We describe 3 cases of M. genavense in patients with HIV representing the spectrum between disease burden and strength of immune response.